Host selection is not a universal driver of phyllosphere community assembly among ecologically similar native New Zealand plant species - Anya S. Noble; Jaber Abbaszadeh; Charles K. Lee (Microbiome)
Abstract Background A growing body of evidence demonstrates that host-associated microbial communities of plant leaf surfaces (i.e. the phyllosphere) can influence host functional traits. However, it remains unclear whether host selection is a universal driver of phyllosphere community assembly. We targeted mānuka (Leptospermum scoparium) and three neighbouring non-mānuka plant species along an 1800-m transect in a New Zealand native bush to conduct a hypothesis-driven investigation of the relative influence of host species identity and stochastic dispersal on the composition of natural phyllosphere bacterial communities. Results We detected significant correlations between host species identity and mānuka phyllosphere communities that are consistent with a dominant role of host selection in the assembly of the mānuka phyllosphere microbiome. In contrast, the phyllosphere community compositions of neighbouring, ecologically similar native plants were highly variable, suggesting that stochastic processes, such as dispersal, had a stronger influence on the phyllosphere microbiomes of those non-mānuka plants compared to the phyllosphere microbiome of mānuka. Furthermore, the distribution of phyllosphere taxa among plant species was congruent with a scenario in which microorganisms had dispersed from mānuka to non-mānuka phyllosphere microbiomes. Conclusions We conclude that host selection of phyllosphere communities is not and should not be presumed to be a universal trait across plant species. The specificity of the mānuka phyllosphere microbiome suggests the presence of functionally significant bacteria that are under direct, possibly chemically mediated, selection by the host. Furthermore, we propose that phyllosphere microbiomes under strong host selection, such as that of mānuka, may act as a source of microorganisms for the phyllosphere microbiomes of neighbouring plants. Video Abstract